Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1038/ajg.2013.242
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Cancer in Pediatric-Onset Inflammatory Bowel Disease: A Population-Based Study

Abstract: In this large pediatric population-based IBD cohort, mortality did not differ from that of the general population but there was a significant threefold increased risk of neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 43 publications
2
39
0
3
Order By: Relevance
“…[34] In our patients the mortality rate was 1.5% (95% CI: 0-3.7%). Peneau et al [35] analyzed the mortality rate in children with IBD in France and found that the mortality rate was 0.84%, which was not different from the rate of the general population.…”
Section: Original Articlementioning
confidence: 97%
“…[34] In our patients the mortality rate was 1.5% (95% CI: 0-3.7%). Peneau et al [35] analyzed the mortality rate in children with IBD in France and found that the mortality rate was 0.84%, which was not different from the rate of the general population.…”
Section: Original Articlementioning
confidence: 97%
“…145 In a pediatric population based cohort of 698 patients with IBD (160 with ulcerative colitis) diagnosed at a median age of 14 and with a median follow-up of 15 years, two patients developed colon cancer. 146 Pediatric gastroenterologists should discuss this complication with families, especially in cases of early onset IBD and during discussion for transition of care to an adult provider. The absolute risk for developing colorectal cancer over a 35 year period was higher if IBD was diagnosed before 15 years of age.…”
Section: Lymphomamentioning
confidence: 99%
“…These data suggest that the risk is low, because only these three cases were identified during a 6-year period in 20 countries, although thiopurine use was common during this period. The second identified, in a cohort of 698 pediatric patients with IBD, nine malignancies during a median follow-up period of 15 years (range 10-17) [36]. The crude rate of cancer was 1.3 %, with a significant threefold increased risk of cancer (SIR 3.0; 95 % CI 1.3-5.9).…”
Section: Malignanciesmentioning
confidence: 98%